Digital gene expression profiling of the transcriptional response to Sclerotinia sclerotiorum and its antagonistic bacterium Bacillus amyloliquefaciens in soybean - Liu, Jianfeng; Hu, Xianwen; He, Hongli; Zhang, Xingzheng; Guo, Jinhua; Bai, Jing; Cheng, Yunqing (Frontiers in Microbiology, 2022)
Soybean Sclerotinia stem rot caused by Sclerotinia sclerotiorum is a common disease in soybean, and effective biological control is urgently needed. We have previously confirmed that Bacillus amyloliquefaciens can effectively antagonize S. sclerotiorum in a plate competition experiment and a soybean seedling inoculation experiment. In this study, the mechanisms underlying plant death caused by S. sclerotiorum and soybean resistance to S. sclerotiorum induced by B. amyloliquefaciens were evaluated. The stems of potted soybean seedlings were inoculated with S. sclerotiorum (Gm-Ss), B. amyloliquefaciens (Gm-Ba), and their combination (Gm-Ba-Ss), using scratch treatments as a control, followed by dual RNA sequencing and bioinformatics analyses. Global gene expression levels in the Gm-Ss treatment were much lower than those in the Gm-Ba, Gm-Ba-Ss, and Gm groups, suggesting that S. sclerotiorum strongly inhibited global gene expression in soybean. In a pairwise comparison of Gm-Ss vs. Gm, 19983 differentially expressed genes (DEGs) were identified. Down-regulated DEGs were involved in various KEGG pathways, including ko01110 (biosynthesis of secondary metabolites), ko01100 (metabolic pathways), ko01120 (microbial metabolism in diverse environments), ko00500 (starch and sucrose metabolism), and ko04075 (plant hormone signal transmission), suggesting that S. sclerotiorum inoculation had a serious negative effect on soybean metabolism. In Gm-Ba vs. Gm, 13091 DEGs were identified, and these DEGs were significantly enriched in ko03010 (ribosome) and ko03008 (ribosome biogenesis in eucaryotes). Our results suggest that B. amyloliquefaciens increases the expression of genes encoding the ribosomal subunit, promotes cell wall biogenesis, and induces systemic resistance. S. sclerotiorum strongly inhibited metabolism in soybean, inhibited the synthesis of the cytoskeleton, and induced the up-regulation of programmed death and senescence-related genes via an ethylene signal transduction pathway. These results improve our understanding of S. sclerotiorum-induced plant death and soybean resistance to S. sclerotiorum induced by B. amyloliquefaciens and may contribute to the improvement of strategies to avoid yield losses.